Evaluating the best interest of a child as a factor influencing the sentencing of the primary caregiver - Ramonyai, Mothekoa Gratitude (University of Limpopo, 2019)
This mini-dissertation seeks to evaluate the best interests of the child as a separate factor that influences the sentencing of a primary caregiver. When a parent is in conflict with the law, the child stands to be affected sentence that the court may impose on the caregiver. A custodial sentence has the potential of affecting the child’s right to parental care. Therefore, in the event where a custodial sentence is appropriate, alternative care of the child by other persons become a possible option. The author recommends that after applying the principles articulated in S v M and making use of a child impact report; the right of the child to parental care should carry more weight. Thus, courts should duly consider the best interest of the child as an independent factor when negative effects to the child are associated with the sentence. Where appropriate, with either a non-custodial sentence or adequate alternative care (in the case of imprisonment).
Thesis (LLM.) -- University of Limpopo, 2019
Keywords: Best interest of the child; Sentencing phase; Sentencing factor; Primary caregiver; Non-custodal sentence; Parental care; Alternative care; 362.0425; Child caregivers; Child care services - Law and legislation